Contemporary Irish Women Poets Memory and Estrangement - Collins, Lucy (Liverpool English Texts and Studies, 2015)
This study examines the intersection of private and public spheres through the representation of memory in contemporary poetry by Irish women. Collins explores how memory shapes creativity in the work of well-known poets such as Eavan Boland, Eiléan Ní Chuilleanáin and Medbh McGuckian as well as in that of an exciting group of younger poets. This book analyses, for the first time, the complex responses to the past recorded by contemporary women poets in Ireland and the implications these have for the concept of a national tradition.